2016
DOI: 10.1097/cej.0000000000000175
|View full text |Cite
|
Sign up to set email alerts
|

Small-area geographic and socioeconomic inequalities in colorectal tumour detection in France

Abstract: The aim of this study was to assess the impact of area deprivation and primary care facilities on colorectal adenoma detection and on colorectal cancer (CRC) incidence in a French well-defined population before mass screening implementation. The study population included all patients aged 20 years or more living in Côte d'Or (France) with either colorectal adenoma or invasive CRC first diagnosed between 1995 and 2002 and who were identified from the Burgundy Digestive Cancer Registry and the Côte d'Or Polyp Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…In accordance with our findings, previous studies have reported that rural residents enter the healthcare system later and with later stages of disease than urban residents [80][81][82][83][84]. Previous research has also found that individuals living in rural areas have limited access to healthcare services [85][86][87][88][89], fewer physician visits per year, and they wait longer for CRC surgery than individuals living in urban areas [57,[90][91][92]. Furthermore, a previous systematic review found that rural residence was associated with patient delay, while practitioners in rural areas were less likely to refer due to the distance from specialist services [93].…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our findings, previous studies have reported that rural residents enter the healthcare system later and with later stages of disease than urban residents [80][81][82][83][84]. Previous research has also found that individuals living in rural areas have limited access to healthcare services [85][86][87][88][89], fewer physician visits per year, and they wait longer for CRC surgery than individuals living in urban areas [57,[90][91][92]. Furthermore, a previous systematic review found that rural residence was associated with patient delay, while practitioners in rural areas were less likely to refer due to the distance from specialist services [93].…”
Section: Discussionsupporting
confidence: 92%